PENGEMBANGAN PERANGKAT PEMBELAJARAN BLENDED LEARNING MODEL COOPERATIVE UNTUK MENINGKATKAN HASILBELAJAR FISIKA SMA KELAS XI - Rosmiati, Rosmiati; Jatmiko, Budi; Madlazim, Madlazim (JPPS (Jurnal Penelitian Pendidikan Sains), 2013)
This research is research development at developing learning material based on blended learning cooperative model. The learning material is developed using Kemp model and one group pretest-posttest design. Try out for learning material is carried out at 2nd semester SMAN 16 Surabaya. The research subjects in grade XI IPA 2, XI IPA 3 and XI IPA 4 and the topic is thermodynamics. Data gathering uses three methods; observation, test and questionnaire. Material validity analysis is applied to analyses data. The validity involve (a) the truth of conseptual in learning material: the reabilitas of learning plans at 85,71%, student?s worksheet at 75%, student?s teks book at 77,27%, web moodle with homepage  http://fisikaunesa.net/elearning/ at 86,34% and assesment sheet for product and process test at 100%, (b) legibility of: student?s worksheet at 99%,  student?s text book at 97,7% and web moodle at 100% in easily understood category, (c) difficulties: student?s worksheet at 1,0; student?s text book at 13,0; Web Moodle at 0,0; and assessment sheet in easily understood category. 2) the practicality involve: (a) realization of Learning Plans reached 100% in good category, (b) student?s activity reached 89% in good category, (c) WIFI?s trouble. 3) the effectivity involve: (a) enhancement  of student?s achievement with N-Gain calculation: Natural Science 2 class with score 0,88, Natural Science 3 with score 0,85, Natural Science 4 with score 0,87 in high category, (b) student?s response with meanin 3 in agree category. Based on the results, it can be concluded that learning material based on Blended Learning Cooperative Model to increase student?s achievement in physics at senior high school grade XI is feasible.Penelitian ini adalah penelitian pengembangan yang mengembangkan perangkat pembelajaran blended learning model kooperatif. Perangkat pembelajaran dikembangkan menggunakan model Kemp dengan model ujicoba one group pretest-posttes design. Uji coba perangkat pembelajaran dilakukan pada semester genap SMAN 16 Surabaya. Penelitian ini dilakukan pada kelas XI IPA 2, XI IPA 3 dan XI IPA 4 materi termodinamika. Pengumpulan data menggunakan tiga teknik yaitu observasi, tes dan angket sedangkan analisis data menggunakan analisis validitas perangkat. Hasil penelitian dianalisis dan diperoleh beberapa temuan yaitu: 1) validitas yang meliputi: (a) kebenaran konseptual perangkat pembelajaran: RPP dengan reabilitas 85,71%, LKS dengan reabilitas 75%, BAS dengan reabilitas 77,27%, web moodle dengan hompage  http://fisikaunesa.net/elearning/ dengan reabilitas 86,34%, dan LP untuk THB produk dan proses dengan reabilitas 100%, (b) keterbacaan: LKS 99%, BAS 97,7% dan  Web Moodle 100% dengan kategori mudah dipahami (c) Kesulitan: LKS 1,0; BAS 13,0; Web Moodle 0,0; dan LP berada pada kategori mudah dipahami. 2) Kepraktisan yang meliputi: (a) Keterlaksanaan RPP mencapai 100% berkategori baik, (b) Aktivitas siswa mencapai 89% berkategori baik, (c) kendala jaringan WIFI. 3) Efektifitas meliputi: (a) Peningkatan hasil belajar dengan perhitungan N- Gain: IPA 2 skor 0,88, IPA 3 skor 0,85, IPA 4 skor 0,87 dengan kriteria tinggi, (b) respon siswa dengan rata -rata 3 berada pada ketegori setuju. Berdasarkan hasil temuan di atas, dapat disimpulkan bahwa perangkat pembelajaran blended learning model cooperative untuk meningkatkan hasil belajar fisika SMA kelas XI layak digunakan.